Angiogenesis and expression of vascular endothelial growth factor and endostatin protein in myocardial infarction rat model - Zheng, Chenglong; Yang, Panchu; Zhang, Lu; Wang, Zhiyong; Chen, Kun; Lan, Yue; Zhai, Xing; Huang, Kun; Guo, Shuwen (Bangladesh Journal of Pharmacology, 2016)
The aim of this study was the effects of supplementing qi and herbs that promote neovascularization on angiogenesis and expressions of vascular endothelial growth factor and endostatin protein in experimentally induced acute myocardial infarction in rats. Left anterior descending coronary artery was ligated to establish the acute myocardial infarction model. Microvascular vascular count and expressions of vascular endothelial growth factor and endostatin protein were detected and indexes were detected at 7th, 14th and 28th day. The results showed large doses of qi herbs combined with small doses of activating herbs are superior to other groups in promoting the angiogenesis, increasing vascular endothelial growth factor protein expressions and reducing endostatin protein expressions. It also showed that there was a dose-response effect of supplementing qi and activating blood circulation herbs promoting angiogenesis. The mechanism of supplementing qi and activating blood circulation herbs and combination of both promoted angiogenesis due to possibly to increased vascular endothelial growth factor protein expressions and reduced endostatin protein expressions.